Pengaruh Metode Penemuan Terbimbing Terhadap Kemampuan Pemahaman Konsep Matematis - Rosyidah, Lailatur; Testiana, Gusmelia; Gustiningsi, Tria (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2019)
This research aims to determine the effect of guided discovery method on the ability to mathematical concept comprehension students of class VIII MTs Islamiyah Trimoharjo OKU Timur. The type of research used is true experimental design. The population of this study consists of 3 classes and selected 2 classes as a sample, namely class VIII.C as experimental class and VIII.A as a control class. Data collection techniques used in this study are the tests as a measure of mathematical concept comprehension and the observation sheet of the implementation of guided discovery method to see the implementation of guided discovery method. Data analysis used is t test with significant level = 0,05, obtained tcritical = 3.285 and ttable = 1,997. The results of the analysis can show that there is influence of the implementation of guided discovery method of learning to students mathematical concept comprehension in the learning of mathematics students of class VIII MTs Islamiyah Trimoharjo OKU Timur.